Technical and Cost Barriers in Accessing Smart Educational Technologies in Rural Areas - Nusrat Jahan (Faculty of Science and Technology, Universitas Sanata Dharma, 2026)
This research study explore how data costs and technical issues affect the use of LowDataMode, based on insights from 100 people living in a resource-limited setting. Using chi-square tests and logistic regression, I analyzed how device types, network access, barriers, and platform usability influence LowDataMode use. Results shows high data consumption (41%) as the primary barrier, significantly linked to LowDataMode use (p = 0.023), with marginal significance in regression (p = 0.086). Technical barriers, including lack of affordable devices (28%) and offline learning options (19%), hinder adoption, particularly for shared family device and laptop/desktop users (p = 0.052). 3G users (55%) face greater data cost challenges, while Wi-Fi users (15%) rarely need LowDataMode. Higher platform usability was associated with a greater likelihood of skipping LowDataMode (β = 1.48, p = 0.008), suggesting that intuitive, feature‑rich apps may encourage more data‑intensive activity and thus raise users’ data costs. And, non-significant was technical barriers include network stability (p = 0.315) and technical problems (p = 0.545).